Pengaruh Media Kartu Bergambar Terhadap Hasil Belajar IPA Siswa Kelas V SD YPK Yeflio Kabupaten Sorong - Lamauran, Lusiana; Rahayu, Desti; Irianti, Mustika (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study was motivated by the low learning outcomes of students, their lack of focus during lessons, and their limited enthusiasm for learning. Therefore, the aim of this research was to determine the effect of picture card media on the science learning outcomes of fifth-grade students at SD YPK Yeflio, Sorong Regency. The research employed a quantitative pre-experimental method with a one-group pretest–posttest design. The sample consisted of 20 students. Data collection technique by distributing a multiple choice test instrument consisting of 20 questions, and the results were analyzed using normality testing and statistical analysis (t-test). The pretest results showed an average score of 60.25, while the posttest results showed an increased average score of 74.75. The t-test results indicated that the calculated t-value was higher than the critical t-value (11.854 1.72913) and the Sig. (2-tailed) value of 0.000 was less than 0.05, leading to the rejection of H0 and acceptance of Ha. Thus, it can be concluded that picture card media has a significant effect on the science learning outcomes of fifth-grade students at SD YPK Yeflio, Sorong Regency.